Short term and dosage influence of palm based medium-and long-chain triacylglycerols on body fat and blood parameters in C57BL/6J mice - Lee, Yee Ying; Tang, Teck Kim; Ab Karim, Nur Azwani; Mohamed Alitheen, Noorjahan Banu; Lai, Oi Ming (Royal Society of Chemistry, 2014)
Structured lipid medium- and long-chain triacylglycerols (MLCT) are claimed to be able to manage obesity. The present study investigated the body fat influence of enzymatically interesterifed palm-based medium- and long-chain triacylglycerols (P-MLCT) on diet-induced obesity (DIO) C57BL/6J mice compared with commercial MLCT oil (C-MLCT) and a control, which was the non enzymatically modified palm kernel and palm oil blend (PKO–PO blend). It also investigated the low fat and high fat effects of P-MLCT. DIO C57BL/6J mice were fed ad libitum with low fat (7%) and high fat (30%) experimental diets for 8 weeks before being sacrificed to obtain blood serum for analysis. From the results, there is a trend that P-MLCT fed mice were found to have the lowest body weight, body weight gain, total fat pad accumulation (perirenal, retroperitoneal, epididymal and mesenteric), total triglyceride levels and efficiency in controlling blood glucose level, compared with C-MLCT and the PKO–PO blend in both low fat and high fat diets. Nevertheless, the PKO–PO blend and P-MLCT caused significantly (P < 0.05) higher total cholesterol levels compared to C-MLCT. P-MLCT present in low fat and high fat dosage were shown to be able to suppress body fat accumulation. This effect is more prominent with the low fat dosage.